STEREOTIPE PASRTISIPASI PEREMPUAN DALAM UNDANG-UNDANG NOMOR 7 TAHUN 2017 PADA PEMILU PEMILU 2024 (GEUNASEH: Jurnal Kajian Gender, Anak dan Sosial Inklusi, 2025)
General elections are an important mechanism in a modern democratic system that allows the people to participate in determining the country's leaders and policies. The main purpose of elections is to provide citizens with the opportunity to express their voices and elect leaders who will represent them in government so that Indonesian women are then able to take a role in politics in Indonesia. The inequality between men and women in politics has resulted in women's aspirations not being channeled through existing political channels, resulting in gender-based political discrimination which has continued for quite a long time.  This research uses normative legal research methods by conducting research studies of literature and statutory regulations related to the research object in order to find answers to the problems to be researched. The results of this research show that after the general election held in 2024, the people have expressed their aspirations through a democratic party held simultaneously throughout Indonesia. The current problem is the paradigm and belief that women's nature is only to take care of the family and women are not suitable to occupy leadership positions. This cannot happen in a democratic country because Article 27 paragraph 1 of the 1945 Constitution (UUD 1945) states that the principle of equal rights for all citizens is recognized without exception, this article as the basis of the State constitution has provided space for every citizen. participate in government without distinction of gender. It is further clarified in article 245 of Law No. 7 of 2017 concerning general elections which states "the list of prospective candidates as intended in article 243 contains at least 30% representation of women. Based on the results of the 2024 election, the number of women's representation only covers 21.9% in DPR RI seats, which means it is not in accordance with the implementation of existing regulations, this is due to the decline in the affirmation policy in the form of a 30% women's nomination quota in PKPU No. 10 of 2023 which carries out rounding down which has the impact of not meeting the minimum number of 30% of women in electoral districts allocated for seats: 4, 7, 8 and 11 which has the potential to reduce the number of women's representation.